Analisis Kualitas Air Perusahaan Daerah Air Minum Unit Anduonohu - Gani, Asnah Junitriani; Rosdiana, Rosdiana; Ndibale, Wa (Universitas Muhammadiyah Kendari, 2022)
The quality of clean water is an important factor in all matters, especially for the Regional Drinking Water Company (PDAM) which will distribute clean water to the community. Maintaining the quality of clean water to avoid contaminants is something the needs to be considered. Therefore, it is necessary to periodically test water quality in order to maintain the quality of clean water obtained, such as testing the level of turbidity and Fe (iron). In this study, the result of the analysis of water quality testing parameters of turbidity and Fe (iron) at each point namely point 1, point 2, point 3, and point 4 had different result. The turbidity level obtained at point 1 (reservoir) was 0,8 NTU, increased at point 2 to 0,81 NTU and again increased at point 3 to 0,82 NTU. Then at point 4, the result obtained are back to 0,8 NTU. While the result of the analysis of the content of iron (Fe) obtained at point 1 (reservoir) is 0,006 mg/L, while at point 2 and point 3 the same results are obtained, namely 0,0052 mg/L, then at point 4 it is much increased to 0,02 mg/L. Things that effect the result of the analysis obtained at each point, including the difference in distance and contours of the soil at each point.